PEMBUATAN MAYONES DENGAN MENGGUNAKAN MINYAK SAWIT MERAH (Red palm oil) DAN MINYAK ZAITUN (Olea europaea) SERTA UJI DAYA TERIMANYA - Henny Afika; Albiner Siagian; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Red palm oil and olive oil can be utilized in making of mayonnaise. The purpose of the study was to determine acceptance of mayonnaise combined with red palm oil and olive oil involve color, aroma, taste, texture and nutrition contents. Research object in this study is mayonnaise combined with three different ratio of red palm oil and olive oil (red palm oil : olive oil 5%:95%; 10%:90%; 15%:85%). This study used experimental design with completely randomized design. Panellists in this study was 30 student of public health in University of Sumatera Utara. Hedonic test data analysis methods used descriptive analysis percentage and statistic tests used friedman test, whereas anlysis of nutrition content used spectrophotometer, HPLC, and GC conducted in PPKS Medan. The study conducted in april until june 2016. The result of this study showed that mayonnaise used red palm oil 15% and 85% preferably with characteristics such as very yellow, distinctive aroma mayonnaise, distinctive flavor mayonnaise, very creamy texture, and contains carotene 296 ppm and vitamin E 175,12 ppm. As a sauce, mayonnaise with red palm oil and olive oil is recommended as contribute daily intake of vitamin A and as one of preventions to vitamin A deficiencies. Keywords: Mayonnaise, Red Palm Oil, Olive Oil, Carotenoids, Vitamin E.